The Role of Adat, the Business World, the Government, and Higher Education Personnel in Urgent Environmental Law Enforcement Efforts to Tackle the Growing Plastic Waste Crisis - Permana, Deni Yusup (Ann Publisher, 2024)
Time perpetually advances, and circumstances evolve, influencing lifestyle modifications. Technological advancements have facilitated a more convenient, practical, and comfortable human existence. The tradition of using plates and spoons, necessitating dishwashing, has been supplanted by a culture of disposable plastic utensils. Plastic garbage is ubiquitous, prompting some communities to declare a waste emergency. A literature review has been conducted on the roles of customs, the business sector, government, and higher education workers in addressing the waste emergency associated with law enforcement initiatives. This study employs a literature review utilizing many data sources, including publications and the Internet. The study results indicate that all community sectors collaborated to address plastic trash, including Indigenous peoples, the corporate sector, central and regional governments, and higher education professionals, each according to their individual capacities. Importantly, public awareness of the need to mitigate garbage accumulation has begun to increase, offering hope for the future. Nonetheless, the issue of inundating plastic garbage resulting from alterations in actual life dynamics remains our responsibility.